Synthesis route to pyrrolones from -cyano ,-unsaturated ketones and -isocyano esters by oxidative dearomatization of 2-aminofuran intermediates - Mahida, Anil K.; Kale, Someshwar B.; Das, Utpal (European Journal of Organic Chemistry, 2017)
An efficient method for the catalyst/promoter-free synthesis of tetrasubstituted furan derivatives proceeding through the [4+1] cycloaddition of isocyanoacetates with electron-deficient olefins was developed. The products were obtained in good to excellent yields without any column chromatography. Oxidative dearomatization of these furans was achieved only in the presence of oxygen, which led to pyrrolones in high yields.